Thermo-mechanical Coupling Simulation Analysis of Cycloid Gear Multi-tooth Form Grinding - Shi Enbing; Su Jianxin; Zhang Lifang; Deng Xiaozhong; Ren Xiaozhong; Cheng Chen (Jixie chuandong)
The cycloid gear multi-tooth form grinding is a gear finishing process，which can finish the processing of three tooth grooves at same time.In the process of high-speed grinding，high temperature will arise on the gear surface instantaneously，which may cause tooth surface burn.The temperature gradient formed by grinding temperature field will cause residual stress on the tooth surface，and the metallographic structure of cycloid gear tooth surface will change，affecting the grinding accuracy of the gear.The finite element method is used to simulate the temperature field of cycloid gear multi-tooth form grinding，and then the thermo-mechanical coupling analysis method is used to obtain the numerical simulation nephogram of the temperature field and thermal stress of cycloid gear form grinding.Through the analysis of the main stress of the grinding area，it can be seen that the stress is mainly concentrated at the grinding center near the root of the tooth，and the grinding area presents hot-pressing stress.In the ground area，the hot-pressing stress is converted into thermal tensile stress and gradually forms residual tensile stress，and the node stress also changes correspondingly with the change of grinding process parameters.The conclusion has certain research significance for predicting the distribution of temperature and thermal stress field during multi-tooth form grinding and reasonably selecting grinding process parameters.